2021
DOI: 10.3389/fphar.2021.723731
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Renal Clearance: What Have We Known and What Will We Do?

Abstract: Augmented renal clearance (ARC) is a phenomenon of increased renal function in patients with risk factors. Sub-therapeutic drug concentrations and antibacterial exposure in ARC patients are the main reasons for clinical treatment failure. Decades of increased research have focused on these phenomena, but there are still some existing disputes and unresolved issues. This article reviews information on some important aspects of what we have known and provides suggestion on what we will do regarding ARC. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 89 publications
(114 reference statements)
0
14
0
Order By: Relevance
“…However, the understanding of the fundamental mechanisms of ARC is incomplete. Currently, three main mechanisms of ARC are widely accepted—namely, SIRS, renal function reserve (RFR), and brain–kidney crosstalk ( Cook and Hatton-Kolpek, 2019 ; Luo et al, 2021 ). Interestingly, all of them appear to be linked to the gut microbiota ( Figure 3 ).…”
Section: Gut–kidney Crosstalk In Sepsismentioning
confidence: 99%
“…However, the understanding of the fundamental mechanisms of ARC is incomplete. Currently, three main mechanisms of ARC are widely accepted—namely, SIRS, renal function reserve (RFR), and brain–kidney crosstalk ( Cook and Hatton-Kolpek, 2019 ; Luo et al, 2021 ). Interestingly, all of them appear to be linked to the gut microbiota ( Figure 3 ).…”
Section: Gut–kidney Crosstalk In Sepsismentioning
confidence: 99%
“…However, ARC in critical care settings is not uncommon [ 4 , 5 ]. This increased renal clearance above the normal range indicates a potential underdosing risk for many renally excreted drugs and contributes to treatment failure [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous ARC studies have reported its developmental mechanisms, prevalence, risk factors, and pharmacokinetics in renally excreted drugs [ 1 6 ]. Although there is a paucity of specific data on dosing regimens in patients with ARC, underdosing of antimicrobials is frequently reported and is an important issue in critically ill patients, where it is more likely to affect therapeutic outcomes [ 7 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified young age, male sex, and illness severity as risk factors associated with the ARC phenomenon. Administration of vasopressor agents and saline loading may also increase the risk of ARC (Udy et al, 2010;Udy et al, 2013b;Luo et al, 2021). Previous studies have observed that patients with ARC have insufficient therapeutic concentrations of antibiotics; therefore, these patients are at a high risk of treatment failure.…”
Section: Introductionmentioning
confidence: 99%